Ulasan Buku ”Il Principe”(Sang Pangeran) Karya Niccolo Machiavelli - Muhammad Boim; Tri Rizky Wulandari; Beany Vas Quin; Amon Qulsepfriti; Adetiya Anggreni; Juwati Juwati; Julika Purwasih; Widiawati Widiawati; Nurliani Nurliani; Wiyah Wiyah; Sasa Sasa; Esyi Esyi (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This review examines the classic book "Il Principe" written by Niccolò Machiavelli. This book became one of the most famous works in the history of political science. by depicting political principles centered on power and governance in a realistic and pragmatic way. Niccolò Machiavelli was a philosopher, writer, diplomat and political thinker who was born in Florence, Italy, on May 3, 1469, and died on June 21, 1527 in Florence. He is known as one of the most important figures in political thought during the Renaissance. “Il Principe" is one of the most famous works written by him. This book was originally published in 1532 and is notable for highlighting human nature, power, and politics. Machiavelli took a realistic and pragmatic approach to politics, considering politics as an arena for power to be exercised with ingenuity and wisdom. In "Il Principe," Machiavelli analyzes historical experience and uses an empirical approach to investigate the actions and decisions of rulers. This book examines practical, albeit controversial, strategies, tactics, and principles of power. Machiavelli describes politics as an art which requires skill and decisiveness.Through this work, Machiavelli highlights the importance of considering the interests of the state and choosing actions that are effective in maintaining power.This book advances the view that political reality is not always in line with moral standards, and leaders Must be able to adapt to changing situations. This review concludes the need to understand political realities and recognize power dynamics to achieve the desired political goals.